Persistent vegetative state after traumatic brain injury - a case report and review of the literature - Rathor, Mohammad Yousuf; Abdul Rani, Mohd Fauzi; Che Abdullah, Shahrin Tarmizi; Hashim, Hasnur Zaman (Ibn Sina Trust, 2014)
Persistent vegetative state (PVS) is a chronic neurological disorder of consciousness, in which patients appear to be awake, but show no behavioural evidence of awareness. It cannot be diagnosed with certainty and misdiagnosis is very frequent. Its management has become one of the most controversial and emotive issues in medical ethics and medical law over the past few decades. The results of recent neuroimaging studies along with well-documented reports of significant late recovery of some PVS patients have challenged the long-held view that restoration of function in the severely traumatic brain injury (TBI) patients is not possible. Some clinicians believe that PVS is a misused term with the potential consequences of withdrawal and withholding of care, and tendency towards less aggressive management. Further naming these patients as “vegetative” has been misinterpreted by many groups that the patient is no more a human but “vegetable” like. Recently there has been an attempt to replace PVS by new, more appropriate name "Unresponsive Wakefulness Syndrome" (UWS). As opposed to brain death, PVS is not recognized by statute as death in any legal system. The context within which end of life decisions are being made for these patients has led to outrage especially if decisions were made to terminate hydration and nutrition. We present a case of young boy who is in a PVS following TBI with the aim to review some of the contemporary issues regarding their management.